Factors Influencing Bolus Dwell Times in Healthy Older Adults Assessed Endoscopically - Butler, Susan G. (2011)
OBJECTIVES/HYPOTHESIS: Scant data exist on normal bolus dwell time assessed during Flexible Endoscopic Evaluation of Swallowing (FEES). The purpose of this study was to examine bolus dwell time in healthy older adults. Since it has been previously reported that some healthy older adults aspirate, we also sought to determine if bolus dwell time varied as function of aspiration status. STUDY DESIGN: Prospective METHODS: Seventy-six healthy volunteers from the 7(th), 8(th), and 9(th) decades of life participated. Dwell times were analyzed via FEES as a function of pharyngeal location, liquid type, delivery method, purée type, viscosity, age, and gender. RESULTS: Longer dwell times were evidenced with the eldest participants, straw delivery, and the smallest volume. Adults in the 9(th) decade were 4.8 (p = 0.01) and 3.8 (p = 0.02) times more likely to have longer dwell times at the vallecula and 7.1 (p = 0.002) and 3.8 (p = 0.02) at the pyriform sinus than those in the 7(th) and 8(th) decades, respectively. Longer dwell times at the vallecula and pyriform sinuses were 2 and 2.38 times (p < 0.0001) more likely for straw than cup delivery, respectively. Five ml boluses were 1.5 times (p < 0.05) more likely to result in longer dwell times than larger volumes. Bolus dwell times did not significantly differ as a function of aspiration status. CONCLUSIONS: Advanced age, straw delivery, and small volumes yielded longer dwell times. These variables should be considered before diagnosing an abnormal bolus dwell time in elder patients.